Adaptations in trabecular bone microarchitecture in Olympic athletes determined by 7T MRI - Chang, G.; Pakin, S. K.; Schweitzer, M. E.; Saha, P. K.; Regatte, R. R. (Journal of Magnetic Resonance Imaging, 2008)
To produce in vivo high-resolution images of the knee and to determine the feasibility of using 7T MR to detect changes in trabecular bone microarchitecture in elite athletes (Olympic fencers) who undergo high impact activity.